Physical and sensory properties of biofortified fresh yellow maize: varietal and harvesting time effects on physical and sensory properties of biofortified fresh yellow maize - Alamu, O.E.; Maziya-Dixon, B.B.; Olaofe, O. (2015)
The effects of processing and harvesting time on the physical and sensory characteristics of micronutrient biofortified yellow maize varieties have been investigated using standard procedures. Freshly harvested eight biofortified yellow maize hybrids and eight open pollinated varieties (OPV) with various endosperm textures were used for this research. Selected fresh harvested yellow maize ears at three maturity stages (20, 27 and 34 days after pollination) were boiled and roasted with or without husk and sensory evaluation was carried out on the boiled and roasted fresh yellow maize samples. Physical characteristics determinations were carried out on the grain of fresh yellow maize samples. The maize samples for colour properties were freeze-dried ,pulverized and sieved to pass through 500μm sieve . The fresh yellow maize flour samples were analysed for colour properties (L*, a* and b*) . The results of the physical characteristic of fresh yellow hybrid and OPV maizes showed highly significant (P􀂔0.001) for the variety and maturity, while only kernel weight, kernel volume, bulk density, kernel size index (KSI), showed significant differences for both fresh yellow hybrid and OPV maizes. There was highly significant effect (P􀂔0.001) for variety, maturity and processing methods (boiling and roasting), on the colour properties for fresh yellow hybrid and OPV maizes. There were increase in the mean values of L*, a* and b* across the maturity stages for fresh yellow hybrid and OPV maizes. The results of the sensory characteristics showed that methods of processing and maturity were important factors in the rating of the sensory attributes of fresh yellow hybrid and OPV maizes. Optimum overall acceptability rating was attained at 20DAP and had the best maturity stages. Consumers slightly preferred boiled OPV maize with husk to that boiled OPV maize without husk. However, consumers showed little or no difference in likeness for boiled hybrid maize with or without husk. However, roasted maize without husk was preferred to roasted maize with husk for fresh yellow hybrid and OPV maizes. There were significant (P􀂔0.001) effects of variety and methods of processing on the antioxidant activity for both fresh yellow hybrid maizes but maturity had no significant effect .The results of the present study could be used by the Maize breeders to further improve the physical characteristics of the maize hybrids and OPVs, and by the consumers to know the best harvest time to consume boiled and roasted maize hybrids.